2015
DOI: 10.1021/la504966y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Potential Well on the Breakage Rate of Colloidal Aggregates in Simple Shear and Uniaxial Extensional Flows

Abstract: In this work we build on our previous paper (Harshe, Y. M.; Lattuada, M. Langmuir 2012, 28, 283-292) and compute the breakage rate of colloidal aggregates under the effect of shear forces by means of Stokesian dynamics simulations. A library of clusters made of identical spherical particles covering a broad range of masses and fractal dimension values (from 1.8 to 3.0) was generated by means of a combination of several Monte Carlo methods. DLVO theory has been used to describe the interparticle interactions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…The yet unraveled interplay between potentials and cluster structures finds here one of its practical outcomes: the nonpossibility to predict the type of breakage and thus the resulting fractal structure for non-DLVO stabilized particles. Recent work based on Stokesian dynamic simulations has however demonstrated that the structure and mass distributions of fragments generated by shearinduced breakage is virtually independent of the depth of the energy well existing between particles in a cluster [72].…”
Section: Interaction Potentialmentioning
confidence: 99%
“…The yet unraveled interplay between potentials and cluster structures finds here one of its practical outcomes: the nonpossibility to predict the type of breakage and thus the resulting fractal structure for non-DLVO stabilized particles. Recent work based on Stokesian dynamic simulations has however demonstrated that the structure and mass distributions of fragments generated by shearinduced breakage is virtually independent of the depth of the energy well existing between particles in a cluster [72].…”
Section: Interaction Potentialmentioning
confidence: 99%
“…This mechanism is generally referred to as orthokinetic aggregation and, for sufficiently large Péclet numbers, enhances the aggregation rate compared to a Brownian mechanism. Furthermore, as aggregates grow in size, the shear stresses exerted by the flow field on the aggregate structure induce substantial restructuring effects, , thus altering the structure produced upon aggregation. For these reasons, if a critical concentration exists in orthokinetic heteroaggregation over which size stabilization occurs, its value may be different from the one characterizing perikinetic aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…This observation can be explained by flow recirculation patterns that demonstrate inertia in the liquid phase, which cannot be completely neglected when simulating particle interactions even at Reynolds numbers considered very low such as Re = 0.028. This is significant information since many numerical investigations in such conditions [ 19 , 31 ] use Stokesian Dynamics, which is unable to account for such effects. They, therefore, cannot be used for calculating inclusion aggregation kinetics.…”
Section: Resultsmentioning
confidence: 99%